Relación entre el Estrés Laboral y las Funciones Ejecutivas. Una Revisión Sistemática 2013 -2023 (2023)
Work stress is a series of stimuli related to psychological, emotional, cognitive and behavioral reactions, in this sense it can be positive and negative. By referring to the concept of stress as a physiological behavior in relation to environmental stimuli, it is possible to identify certain professional, family and personal consequences when some entities such as the WHO. (world health organization), decided to make known the problems presented at the Latin American level and the relationship with different work environments. Therefore, the documentary review was carried out with the prism method where it was possible to analyze 13 articles in which the investigation of the effects that work stress has on executive functions was addressed, therefore it was possible to conclude certain effects, affecting working memory, inhibition and work planning.